(1)16 x ² - 4 y ²
= (4 x + 2 y)(4 x - 2 y)
= 4(2 x + y)(2 x - y)
(2)(a ² - 2 a b + b ²)- 4
= (a - b)² - 4
= (a - b + 2)(a - b - 2)
(3)m ² (x - y)+ n ² (y - x)
= m ²(x - y)- n ² (x - y)
= (x - y)(m ² - n ²)
= (x - y)(m + n)(m - n)
(4)(x ² + y ²)² - 4 x ² y ²
= (x ² + 2 x y + y ²)(x ² - 2 x y + y ²)
= (x + y)²(x - y)²
(5)a ^ 4 - 2 a ² b ² + b ^ 4
= (a ² - b ²)²
= 【(a + b)(a - b)】²
= (a + b)²(a - b)²
(6)2 a ^ 4 - 4 a ² + 2
= 2(a ^ 4 - 2 a ² + 1)
= 2(a ² - 1)²
= 2【(a + 1)(a - 1)】²
= 2(a +1)²(a - 1)²